2017
DOI: 10.1038/nature23014
|View full text |Cite|
|
Sign up to set email alerts
|

A novel mechanism for mechanosensory-based rheotaxis in larval zebrafish

Abstract: When flying or swimming, animals must adjust their own movement to compensate for displacements induced by the flow of the surrounding air or water1. These flow-induced displacements can most easily be detected as visual whole-field motion with respect to the animal’s frame of reference2. In spite of this, many aquatic animals consistently orient and swim against oncoming flows (a behavior known as rheotaxis) even in the absence of visual cues3,4. How animals achieve this task, and its underlying sensory basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
218
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(236 citation statements)
references
References 26 publications
16
218
1
1
Order By: Relevance
“…Only one neuromast and its afferents lacked contralateral counterparts. This may be an important anatomical feature that facilitates comparisons of local velocity vector fields for detecting differential flow along the left and right sides, which is essential for larval zebrafish rheotaxis behaviour 28 .…”
mentioning
confidence: 99%
“…Only one neuromast and its afferents lacked contralateral counterparts. This may be an important anatomical feature that facilitates comparisons of local velocity vector fields for detecting differential flow along the left and right sides, which is essential for larval zebrafish rheotaxis behaviour 28 .…”
mentioning
confidence: 99%
“…Based on their behavioural data, Oteiza et al . () proposed a model, suggesting that fish use their mechanosensory lateral‐line system to first sense the local curl in the water ( i.e ., local rotations of the water) to detect the presence of flow and then to measure the temporal change of these curls after the swimming bouts to deduce flow direction.…”
Section: Adaptations Of the Lateral‐line System For Orientation In Wamentioning
confidence: 97%
“…Sutterlin and Waddy () suggested that the lateral‐line system serves as a detector of flow or pressure discontinuities, enabling the fish to maintain position with minimum expenditure of energy. This is in agreement with the mechanism proposed to underlie rheotaxis in A. mexicanus and D. rerio (Kulpa et al ., ; Oteiza et al ., ), However, whereas these two species rely on hydrodynamic information received by SNs, O. mykiss may rely mostly on information picked up by CNs. Sensing flow discontinuities with both lateral‐line subsystems is possible since the water motions behind an object contain discontinuities both in velocity and acceleration, which will be measured by SNs and CNs, respectively (Coombs et al ., ; Montgomery et al ., ).…”
Section: Adaptations Of the Lateral‐line System For Orientation In Wamentioning
confidence: 97%
See 1 more Smart Citation
“…But how does the lateral line sense local patterns of water motion, and how do fish use that information to navigate? On page 445, Oteiza et al 3 propose an elegant mechanism based on a robust principle of fluid dynamics, which only requires the fish to respond to the flow by making a simple choice between either continuing to swim without changing direction or making a turning manoeuvre.…”
mentioning
confidence: 99%